Assessment of pain, acceptance of illness, adjustment to life with cancer, and coping strategies in colorectal cancer patients - Czerw, Aleksandra; Religioni, Urszula; Deptała, Andrzej; Walewska-Zielecka, Bożena (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Introduction : Every year more than 15,000 newly diagnosed cases of colorectal carcinoma are recorded in Poland. Aim : The objective of the study was an assessment of coping strategies and pain management, acceptance of illness, and adjustment to cancer in patients diagnosed with colorectal carcinoma. The analysis was extended to include the effect of socioeconomic variables on the above-mentioned issues. Material and methods : The study included 238 colorectal cancer patients treated on an outpatient basis at the Centre of Oncology, the Maria Skłodowska-Curie Institute in Warsaw in the year 2013. The questionnaire interview comprised demographic questions (socioeconomic variables) and the following four psychometric tests: BPCQ (Beliefs about Pain Control Questionnaire), CSQ (Coping Strategies Questionnaire), AIS questionnaire (Acceptance of Illness Scale), and the Mini-Mac scale (Mental Adjustment to Cancer). Results : The source of pain control depends on the respondent’s level of education. An increase in patient income was associated with a lower mean result in the “power of doctors” subscale. The coping self-statements and increased behavioural activity are the two most frequently selected strategies of coping with pain. The most commonly followed ways of mental adjustment to cancer in the study group were a fighting spirit (23.42) and positive re-evaluation (22.31). Conclusions : Colorectal cancer patients believe that the greatest role in pain management is played by internal factors. The locus of pain control depends on the level of education. The study patients feature a constructive way of struggling with disease differentiated by the place of residence, professional status, and income.